Comparative Analysis of Learning Methods and Their Influence on Enthusiasm and Level of Focus at SMP PGRI Karawang - Fazrian Thursina (The Eastasouth Journal of Learning and Educations, 2023)
This study aims to determine the comparative effectiveness of the implementation of two different learning methods, namely conventional learning methods (lectures) with technology-based learning methods (video-based learning/vbl), on enthusiasm and the level of focus of class VIII A students at SMP PGRI Karawang in the process of absorbing social science teaching materials chapter on conflict and integration in social life and its influence on student learning outcomes. This type of research is experimental research. This research was conducted at SMP PGRI Karawang, and the sample was VIII A class students determined by a simple random sampling technique. Data collection uses tests and questionnaires. The validity of the instrument is measured by calculating the percentage.